An Analysis of the Impact of Socioeconomic Disadvantage and School Quality on the Probability of School Dropout - Stéphane Mahuteau; Kostas G. Mavromaras (Institute for the Study of Labor (IZA), 2013)
PISA scores are an internationally established indicator of student and school performance. This paper builds on the evidence that better PISA scores are known to be associated with better later life outcomes. It uses the Australian PISA micro-level data in combination with its longitudinal continuation in the LSAY data, to measure the degree to which individual PISA scores are associated with individual early school dropouts. It distinguishes between student and school factors and estimates a model of the propensity to drop out from school between ages 15 and 18. The paper finds that PISA scores are a good predictor of early dropout, and that individual and social disadvantage plays a crucial role in this relationship both directly and indirectly.
Keywords: I24; I21; 330; PISA; socioeconomic disadvantage; school dropout; student outcomes; multilevel modelling